(In)VERSÕES POLÍTICO-ESCATOLÓGICAS NO PENTECOSTALISMO BRASILEIRO Uma análise da posição e ação política das Assembleias de Deus de 1930-1945 e 1978-1988 a partir do jornal Mensageiro da Paz - CARVALHO, OSIEL LOURENÇO DE, (2016)
This research analyzed the political position and action in the Assemblies of God of Brazil in the periods 1930-1945 and 1978-1988. We defend the thesis that since 1930 there within the Brazilian Pentecostalism positions and interventions in the world of politics. In both the 1930-1945 period and the 1978-1988 our analyzes will be carried out from the time frames discussed by Giorgio Agamben: chronos, Aion is kairos. With regard to the first period 1930-1945, research almost always binding on the eschatological discourse of Pentecostalism alienation processes and not involved with party politics. However, it is believed that the eschatological narratives were not sure because of remoteness of the Brazilian public sphere, but the effect of the exclusion of processes to which men and women belonging Pentecostal been circumscribed. Doctrines such as eschatology and pneumatology were potentiating processes that here we call biopotency. In the second period, from 1978-1988, the position and political action that prevailed in Pentecostalism were related to biopolitics. Call intermedário chapter or transition the corresponding period the dates 1946-1977. We will describe and analyze prominent Pentecostal personalities in the field of Brazilian politics. Methodologically, we did our analysis from articles published in the official communication of the religious denomination concerned, the Messenger Journal of Peace. This newspaper circulates since 1930. In addition to the articles also highlight the authors and authors, all of them and all of them leading figures in assembleianismo. During the research question the idea of the Pentecostal apoliticism. We defend the thesis that since 1930, which is the beginning of our research, there are political position and action in the Assemblies of God. As a result, we question the idea of the Pentecostal apoliticism. Our hypothesis is that in the period 1930-1945 Pentecostalism was a center of biopotency. If biopolitics is the power over life, biopotency is the power of life. Doctrines such as eschatology and pneumatology contributed to the marginal spaces where they met the Pentecostals were created new models of sociability and cooperation; They were also spaces to create other narratives and criticism of hegemonic and exclusive models. Pentecostalism was a movement that promoted the human dignity of subaltern subjects.